Annual report - Family Responsibilities Commission (Cairns, Qld. : Family Responsibilities Commission, 2009)
The Family Responsibilities Commission began operation on 1 July 2008 as a key component of the Cape York Welfare Reform objective of restoring social norms in Indigenous communities. The FRC will cease operations on 1 January 2012. The 4 Cape York communities within the FRC's jurisdiction are Aurukun, Coen, Hope Vale and Mossman Gorge and the FRC applies to Aboriginal and non-Aboriginal community members who are welfare recipients who reside or have lived in one of the 4 CYWR trial communities for 3 months since 1 July 2008.
Title from cover.
Also available online. Address as at 5/2/18
Keywords: Family Responsibilities Commission -- Periodicals; Aboriginal Australians -- Queensland -- Cape York Peninsula -- Social conditions -- Periodicals; Social welfare; Government policy - State and territory - Queensland; Government policy - Intervention - Emergency response - 2007-2012.; Child welfare; Coen (Qld NE Cape York SD54-08); Cape York map area (Qld TSI SC54-12); Mossman Gorge (NE Qld SE55-01); Hope Vale (Qld SE Cape York SD55-13); Aurukun (Qld NW Cape York SD54-07); Australian